Environmental challenges in the Kurdistan Region: The impact of environmental changes on geographical identity - Palani, L.Dr. Nakhshan Muhammad Rustam Khan (Sulaimani Journal for Humanities, 2025)
The Kurdistan Region is characterized by a diverse geographical landscape, which has historically shaped the livelihood of its inhabitants, primarily based on agriculture and livestock grazing. However, in recent decades, the region has experienced rapid environmental changes, the most significant of which is the rise in temperatures. Data indicates that the average temperature increased by )1.7°C( between )2009 and 2022(, with the highest recorded increase of )2.1°C( in both Sulaymaniyah and Duhok. Additionally, the region suffers from fluctuating rainfall patterns, exacerbating issues of drought and desertification. These environmental changes have directly impacted natural resources, as agricultural lands in some areas, such as )Garmian and Halabja(, have witnessed a sharp decline in productivity. This, in turn, has led to increased rural-to-urban migration, reshaping the region’s demographic composition. This research aims to analyze the environmental challenges facing the Kurdistan Region and their impact on its geographical identity through a descriptive and analytical geographical approach. The study relies on official data, reports from international organizations, and academic research. Furthermore, it discusses the efforts undertaken to mitigate these environmental impacts. The findings confirm that environmental changes pose a direct threat to the geographical identity of the Kurdistan Region by altering land-use patterns, affecting economic activities, and increasing environmental migration rates. Based on these findings, the study recommends adopting adaptive strategies, including enhancing sustainable environmental policies, investing in renewable energy projects, and strengthening regional cooperation for more efficient water resource management.
Keywords: Environmental challenges; Kurdistan Region; climate change; water scarcity; geographical identity